DETECTION OF NON-INFLUENZA VIRUSES IN ACUTE RESPIRATORY INFECTIONS IN CHILDREN UNDER FIVE-YEAR-OLD IN COTE D’IVOIRE (JANUARY – DECEMBER 2013) - Kadjo, Herve A.; Adjogoua, Edgard; Dia, Ndongo; Adagba, Marius; Abdoulaye, Ouattara; Daniel, Saraka; Kouakou, Bertin; Ngolo, David C.; Coulibaly, Daouda; Ndahwouh, Talla Nzussouo; Dosso, Mireille (African Journal of Infectious Diseases (AJID), 2018)
Background: Influenza sentinel surveillance in Cote d’Ivoire showed that 70% of Acute Respiratory Infections (ARI) cases remained without etiology. This work aims to describe the epidemiological, clinical, and virological pattern of ARI that tested negative for influenza virus, in children under five years old. Materials and Methods: one thousand and fifty nine samples of patients presenting influenza Like Illness (ILI) or Severe Acute Respiratory Infections (SARI) symptoms were tested for other respiratory viruses using multiplex RTPCR assays targeting 10 respiratory viruses. Results: The following pathogens were detected as follows, hRV 31,92% (98/307), hRSV 24.4% (75/329), PIV 20.5% (63/307), HCoV 229E 12,05% (37/307), hMPV 6.2% (19/307), HCoVOC43 1.0% (3/307) and EnV 1.0% (3/307). Among the 1,059 specimens analyzed, 917 (86.6%) were ILI samples and 142 (23.4%) were SARI samples. The proportion of children infected with at least one virus was 29.8% (273/917) in ILI cases and 23.9% (34/142) in SARI cases. The most prevalent viruses, responsible for ILI cases were hRV with 35.89% (98/273) and hRSV in SARI cases with 41.2% (14/34) of cases. Among the 1,059 patients, only 22 (2.1%) children presented risk factors related to the severity of influenza virus infection. Conclusion: This study showed that respiratory viruses play an important role in the etiology of ARI in children. For a better understanding of the epidemiology of ARI and improved case management, it would be interesting in this context to expand the surveillance of influenza to other respiratory viruses.